Why group mental states are not exhaustively determined by member states. - Epstein, Brian (Philosophical Issues, 2022)
To speak of the "constitution" of the buildings' state of displaying the Barnes Collection is even a bit stranger than to speak of the constitution of the state of the one building displaying I Le Bonheur de Vivre i . Yet at any given time, certain bits of paint and canvas are part of the constitution of I Le Bonheur de Vivre i .[9] Matisse is not and never was part of the constitution of I Le Bonheur de Vivre i . (Theiner, [40], p. 197) In these two articles, neither Tollefsen nor Theiner addresses hybrids. That is, scientific knowledge at I t i fails to be exhaustively determined by knowledge states of individuals at I t i (i.e., by synchronic knowledge states). Still, that state is in part I ontologically determined i by Matisse, who is not part of the constitution of the Barnes Foundation Building (or I a fortiori i , of the constitution of I Le Bonheur de Vivre i ).